Prevalence of restless legs syndrome and sleep quality in carriers of the fragile X premutation. (2nd September 2013) - Summers, S.M.; Cogswell, J.; Goodrich, J.E.; Mu, Y.; Nguyen, D.V.; Brass, S.D.; Hagerman, R.J.
<x xml:space="preserve">Abstract</x> This study examined the relationship between the fragile X premutation and restless legs syndrome (RLS). Demographic, medical history and survey responses related to sleep were collected from 213 participants (127 carriers and 86 age matched controls). Subjects were asked about the presence of the four formal diagnostic criteria for RLS. Individuals with the premutation were 1.9 times as likely to meet criteria for RLS (95% CI 1.1–3.2, p = 0.025) as controls. Premutation carriers with RLS also experienced significantly worse symptoms than matched controls with adjusted mean scores of 15.1 ± 8.8 vs 7.9 ± 4.4, respectively on the International Restless Legs Scale (IRLS). As markers for domains of sleep disturbance, all subjects completed the Epworth Sleepiness Scale (ESS), the Insomnia Severity Index (ISA) and the Pittsburgh Sleep Quality Index (PSQI). Premutation carriers demonstrated significantly more pathology on these tests except for the ESS where there was a trend towards increased daytime sleepiness in carriers. RLS joins a host of other conditions that should be carefully screened for in those carrying the fragile X premutation and sleep should be a focus for clinicians providing care to them.